Linear Velocity of Cyclic Adenosine 3′,5′-Monophosphate Transport in Corn Coleoptiles - Sherwin, John E. (1974)
The transport of cyclic adenosine 3′, 5′-monophosphate in corn coleoptile segments is very rapid. The linear velocity of basipetal transport is 183 millimeters per hour, while the velocity of acropetal transport is 79 millimeters per hour. Transport velocity as well as intensity thus appear to be polar in the corn coleoptile. Application of metabolic inhibitors such as cyanide, ouabain, and 2,4-dinitrophenol increase rather than decrease the velocity and intensity of transport. The mechanism of transport in light of these data is discussed.